Geography of World Pilgrimages Social, Cultural and Territorial Perspectives - Lopez, Lucrezia (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book points out how pilgrimage studies rely on interdisciplinary academic interests, being always more determined by anthropological, social, cultural and economic factors. The volume gathers interdisciplinary contributions revealing different approaches and academic interests when researching pilgrimage. Finally, the proposal introduces a comparative international breath to reflect upon such complex phenomenon that since Antiquity still impregnates the history of human being across the world. As pilgrimage studies are closely related to mobility issues, how the contemporary mobile world is altering and re-signifying pilgrimage dynamics and meanings will also be discussed in detail. The term "pilgrimage" evokes key concepts deriving from different fields, all of them collected in the final glossary. The primary audience of this work are academics and researchers from different fields involved in pilgrimage studies. The work may also be useful in teaching (advanced) university courses.
Introduction: Geography of World Pilgrimages. Social, Cultural and Territorial Perspectives -- After the Journey. Marian Shrines as Spatial Nodes in Papal Pilgrimage and Communication -- Pilgrimage in Southern Africa: Socio-Cultural Perspectives within the Context of African Religion -- Network of Saints, Network of Roads. Apulia Crossroads of Pilgrimages -- Sacred Space in Geography: Religious Buildings and Monuments -- Prayer of the Body: Located Corporeal Practices on The Lough Derg Pilgrimage, Ireland -- The Psychological 'Geography' and Therapeutic 'Topography' of the Norwegian St. Olav Way -- Sacred Mobilities, Movement, and Embodiment in the 20th & 21st Century English Christian Funeral Procession -- The Ancient Routes of Kumano in Japan as a Cultural Landscape: A Multidimensional Approach -- Maya Pilgrimage, Ritual Landscapes, and Relations with Deities in Chiapas, Mexico -- The Post-Contemporary Way of St. James and Its Future -- (Re)Invention of the Way of Saint James between Religion and Poetry: The Way of Faith and the Way of Cora Coralina in Brazil -- Planning a Pilgrimage Route: Public Policies and Actors to Develop the Via Francigena in Italy -- Geography of Hindu Pilgrimage Places (Tīrthas) in India -- Pilgrimage During The COVID-19 Pandemic: Do Mitigation Plans Lead to Greening the Pilgrimage? -- Glossary.
Keywords: Geography; Human geography; Cultural geography; Ethnology; Religion; Regional Geography; Human Geography; Social and Cultural Geography; Sociocultural Anthropology; Religion